Polymorphisms of Human Leukocyte Antigen Genes in Korean Children with Kawasaki Disease - Oh, Jin Hee (Springer-Verlag, 2007)
BACKGROUND: Kawasaki disease is a leading cause of acquired heart disease in children. The prevalence rate varies in different ethnic groups. Recently, with the clinical application of molecular genetic technology, human leukocyte antigen (HLA) polymorphisms associated with several diseases have been identified by DNA analysis. This study aimed to assess the association of HLA alleles with susceptibility and complications of Kawasaki disease in Korean children. METHODS: In this study, DNA was extracted from 74 children with a diagnosis of Kawasaki disease. The polymorphisms of the HLA-A, -B, -C, and -DRB1 alleles of patients with Kawasaki disease were determined by polymerase chain reaction (PCR)–amplification refractory mutation system (ARMS) and PCR–sequence-specific primer (SSP) analysis. The polymorphisms identified were compared with those of 159 normal healthy control subjects. RESULTS: There was a significant increase in the frequencies of the HLA-B35, -B75, and -Cw09 alleles in patients with Kawasaki disease compared with the healthy control group. There was no increase in the frequency of HLA-DRB1 alleles among the Kawasaki disease patients compared with a healthy control group. When the patients with Kawasaki disease were divided into two subgroups, with or without coronary complications, the Kawasaki disease patients with coronary complications showed a significantly increased frequency of the HLA-DRB1*11 allele compared with the healthy control group and increased frequency of HLA-DRB1*09 in a comparison of the subgroups. CONCLUSIONS: This study suggests that polymorphisms in some alleles of B and C in HLA class I genes are associated with Kawasaki disease in Korean children.